(untitled) (Global Journal of Science Frontier Research, 2017)
Glutelin protein is the most well-known abundant seed storage protein in rice seed endosperm. A total of 9 glutelin and glutelin type protein sequences from Oryza species available in uniport were evaluated by using bioinformatics tools to investigate physico-chemical properties, secondary structure prediction, putative phosphorylation sites and conserved motif search. Physicochemical analysis offers data such as pI, EC, Al, GRAVY and II about these sequences and the results showed that all glutelin protein sequences are basic, hydrophilic, thermo stable, having some extracellular portion. The secondary structure of the protein sequences were also predicted using SOPMA server. It was observed that alpha helix was predominant, followed by random coil, extended strand and least beta turn was found. Putative phosphorylation sites were also identified which are found to be conserved in plant species and the results showed that the most abundant phosphorylation site is serine residues in glutelin protein sequences.